2014
DOI: 10.1037/a0037340
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of delay discounting behavior in adolescence: A longitudinal twin study.

Abstract: A standard assumption in the delay discounting literature is that individuals who exhibit steeper discounting of hypothetical rewards also experience greater difficulty deferring gratification to real-world rewards. There is ample cross-sectional evidence that delay discounting paradigms reflect a variety of maladaptive psychosocial outcomes, including substance use pathology. We sought to determine whether a computerized assessment of hypothetical delay discounting (HDD) taps into behavioral impulsivity in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…As observed in the younger, no/low-drinking youth, the exceeds-threshold drinking youth, who were generally in the older age range, exhibited a preference for a smaller, more immediate award at the expense of a larger delayed reward. The pattern of discounting behavior exhibited by the exceeded-threshold youth is typical of heavy drinking adolescents and may convey some ongoing risk for real-world temporal discounting (Isen, Sparks, & Iacono, 2014; Stanger et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…As observed in the younger, no/low-drinking youth, the exceeds-threshold drinking youth, who were generally in the older age range, exhibited a preference for a smaller, more immediate award at the expense of a larger delayed reward. The pattern of discounting behavior exhibited by the exceeded-threshold youth is typical of heavy drinking adolescents and may convey some ongoing risk for real-world temporal discounting (Isen, Sparks, & Iacono, 2014; Stanger et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates a genetic contribution to the degree of delay discounting, because both types of twins have similar environmental influences on delay discounting, yet the correlation was stronger in twin pairs sharing more genes. Subsequent studies have replicated and extended these findings (Anokhin, Grant et al, 2015; Isen et al, ; Sparks et al, ). Although the studies with twins indicate that delay discounting has a heritable component, the search for the particular loci associated with delay discounting remains ongoing (see MacKillop et al, ), and is beyond the scope of this review.…”
mentioning
confidence: 86%
“…Field et al (2007) showed that heavy drinkers in late adolescence were more likely to discount hypothetical monetary and alcohol rewards than light drinkers in late adolescence. However, another longitudinal study failed to identify a significant association between early adolescence delay discounting rates and drug use problems in late adolescence (Isen et al, 2014). Regarding tobacco use, several studies have shown steeper discounting rates in adolescent cigarette smokers (Audrain-McGovern et al, 2004; Audrain-McGovern et al, 2009; Reynolds et al, 2007), although the effect seems to be smaller than adults (Reynolds et al, 2004).…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%